Relational Values of Grammatical Features on Docudrama Social Dilemma: A Critical Discourse Analysis - Rina Mulya (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
This study focused on the relational values of grammatical features in the docudrama film The Social Dilemma. The Social Dilemma is a docudrama that was released on Netflix in 2020 and it is the combination of documentary-style interviews with experts in the fields of technology, social media, and psychology, as well as dramatized sequences that illustrate the potential negative impacts of social media and technology on society. Relational values in critical discourse analysis (CDA) refer to how language is used to construct and negotiate social relationships between different groups and individuals. To conduct this study, the researcher used the main theory from Fairclough (2013) that focused on three grammatical features of the text: modes of sentence, modality, and pronouns. This study aims to understand how language is used to construct and maintain social relationships, to reveal the power dynamics that underlie communication in society, particularly in the docudrama film The Social Dilemma, and to describe it in the discussion. This study only analyzed the grammatical features of text expressed by some interviewees. This study used descriptive qualitative which is very common for conducting research in social sciences. This study also used critical discourse analysis (CDA) to provide a critical perspective on language use and its role in shaping social realities, power relations, and ideologies.